What Predict Modern Contraception Use? A Study of Reproductive Age Married Couples in Indonesia - Dian Jayantari Putri K Hedo; Nicholas Simarmata (Jurnal Promosi Kesehatan Indonesia, 2023)
ABSTRACTBackground: Health, including reproductive health is everyone's right. Reproductive health can be achieved in several ways, including the practice of family planning through modern contraception used by married couples. Modern contraception brings positive impact for ensuring couples and families’ overall health and wellbeing. However, prevalence of modern contraception use among couples is still low, including in Indonesia. This study aimed to determine factors that predicted the modern contraception use of reproductive age married couples in Indonesia.Method: This study was quantitative study with cross-sectional approach. Data used in this study was secondary data from the 2021 Family Data Collection. Sampling technique was saturated sampling on reproductive age couples in 34 Provinces in Indonesia. Dependent variable was modern contraception use. Independent variables were women's ideal marriage age, women's early marriage age, and ideal number of children preferences. Data analysis used multiple linear regression test. Results: Results showed that variables that were significantly related to modern contraception use were women's ideal marriage age, women's early marriage age, and ideal number of children preferences (p<0.001). There was significant relationship between each variable women's ideal marriage age (p<0.001), women's early marriage age (p<0.001), and ideal number of children preferences (p<0.001) with modern contraception use. women's ideal marriage age, women's early marriage age, and ideal number of children preferences were predictors of modern contraception use among reproductive age married couples in Indonesia, both simultaneously and individually. Based on study results, reproductive age couples need to consider their age of marriage and gain good information and understanding about children preferences. It is hoped that it would increase their participation of modern contraception use.